Detection of Antibodies against Tick-Borne Encephalitis Virus in Zoo Animals Using Non-Invasive Blood Sampling with Medicinal Leeches (Hirudo medicinalis) - Kvapil, Pavel; Kastelic, Marjan; Jež, Nuša; Sedlák, Kamil; Kašpárková, Nikola; Jelovšek, Mateja; Avšič-Županc, Tatjana; Bártová, Eva; Račnik, Jožko (Pathogens (Basel, Switzerland), 2021)
Reports on non-invasive blood sampling are limited, and there are only a few studies on using kissing bugs (Reduviidae) and medicinal leeches (Hirudo medicinalis) for hematology and biochemistry testing in various zoo animal species. The aim of this study was to evaluate the usefulness of non-invasive blood sampling with medicinal leeches for arbovirus epidemiological investigations in various animal species from one zoo collection. Medicinal leeches were manually applied on 35 animals of 11 species. Control blood samples were obtained by venipuncture of the jugular vein. Antibodies to tick-borne encephalitic virus (TBEV) were detected by using the immunoenzymatic method or an immunofluorescent assay (IFAT), depending on the animal species. One of the 35 animals (2.9%) was seropositive (Ovis aries), whereas the rest of the samples were seronegative in both methods of sampling (non-invasive by leeches vs. invasive by venipuncture). Blood sampling using medicinal leeches showed promising results. It is likely a good alternative to other more complex and invasive methods, and it can provide significant advancement in blood sampling for preventive medicine and epidemiological studies in zoo animals.
Keywords: infectious disease monitoring; epidemiology; animal welfare